Mapping of Dengue Hemorrhagic Fever in the Kupang City Community Health 2019-2021 - Wanti, Wanti; Irfan, Irfan; Fantiana Suryanti; Irwan Budiana; Ety Rahmawati; Oktofianus Sila; , Muhammad Satria Mandala Pua Upa; Maria Hilaria (Poltekkes Kemenkes Kupang, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease transmitted through the bite of the Aedes aegypti mosquito infected with the dengue virus. DHF cases increase annually and are endemic in almost all regions of Indonesia. The purpose of this study was to determine the distribution of DHF cases at Kupang City Community Health Centers (Puskesmas) in 2019-2021 based on village characteristics, gender, and age. The method used in this study was descriptive, with the variables of DHF mapping based on village, gender, and age. The study sample consisted of all DHF patient data registered in the registration book at Kupang City Community Health Centers (Puskesmas) in 2019-2021. The collected DHF patient data is presented in map form. The data show that male patients outnumber female patients, with the highest age group being 5-9 years old. Of the five villages, Merdeka Village had the highest number of cases in 2019-2021